Retrospective Analysis of Poisoning Cases Admitted to Kayseri City Hospital Adult Emergency Department as a Result of Suicidal Attempt by Drug Ingestion - Taner Sahin; Nihal Koç; Onur Türkön; Hasan Tüle; Ahmet Ceylan; Mehmet Ali Bilgili (Van Tıp Dergisi, 2021)
INTRODUCTION: Suicide attempts and suicide acts are a severe cause of morbidity and mortality for individuals. In the study, It is aimed to retrospectively examine the patients over 18 years of age who applied for suicidal attempts due to excessive drug intake and to describe the characteristics of the patients, causes and consequences of the suicide attempts. METHODS: In this study, 615 patients with suicide attempts due to excessive drug intake over the age of 18 who applied to the emergency service of Kayseri City Hospital by an ambulance or outpatient within one year were included. While analyzing the data; descriptive statistics were presented with frequency and percentage values. p <0.05 was considered statistically significant. RESULTS: Mean age was 30.93+-11.41(min: 18-max: 85). Of the cases, 63.3% were female, 62.9% were married. Of the cases, 82.9% had not previously attempted suicide and 33% had received psychiatric treatment in the past six months. The rates of attempted suicide were higher among women in the study(p= 0.01, p<0.05). In the last six months, the suicide attempt rates of those receiving psychiatric treatment were higher(p= 0.01, p<0.05). 42.1% of cases found to have attempted suicide by taking multiple drugs. DISCUSSION AND CONCLUSION: The rate of repeat suicide attempts is high for patients who refuse to be treated or hospitalized in emergency departments and hospitals. For this reason, we recommend that the patients with suicide attempts who applied to emergency departments be consulted to the psychiatrist before discharging from emergency services and, if possible, they should be hospitalized.